Double-core evolution and the formation of neutron-star binaries with compact companions - Dewi, J; Podsiadlowski, P; Sena, A (2006)
We present the results of a systematic exploration of an alternative evolutionary scenario to form double neutron-star binaries, first proposed by Brown (1995), which does not involve a neutron star passing through a common envelope. In this scenario, the initial binary components have very similar masses, and both components have left the main sequence before they evolve into contact; preferably the primary has already developed a CO core. We have performed population synthesis simulations to study the formation of double neutron star binaries via this channel and to predict the orbital properties and system velocities of such systems. We obtain a merger rate for DNSs in this channel in the range of 0.1 - 12/Myr. These rates are still subject to substantial uncertainties such as the modelling of the contact phase.